Covid-19 preventive measures for the return to school: Documents from 13 Countries - Soares, Letícia (2020)
Policies of social isolation responding to the SARS-CoV-2 pandemic have led to the closing of schools in more than 190 countries. Schools are organizing their structure and functioning so that the reopening takes place in the safest way possible. The purpose of this article is to list the biosafety measures adopted by other countries when returning to classes for students aged 10 to 19 years. Protocols for reopening educational institutions in 13 countries were analyzed. Provisions were identified regarding who can attend school, personal hygiene and school cleaning, wearing masks and social distancing. The reopening of schools must take into account the epidemiological situation of each region and the infrastructure conditions of each institution.